Sejarah Perkembangan Perbankan Syariah di Indonesia dan Dunia - Ihsan Mustafa; Alip Gumilar; Prili Fatya Wahdiana; Najwa Ghefira Nabilla; Amelia Anggraini Saputri; Ghina Dwi Wardatul F; Cindy Nabilla Pasha (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
Islamic banking is a financial system that operates in accordance with the principles of Islamic law, such as the prohibition of usury (riba), gharar (unlawful betting), and maisir (gambling), as well as the implementation of a profit-sharing mechanism. Islamic banking was born in the 1960s with the founding of Egypt's Mit Ghamr Savings Bank as a pioneer, followed by the establishment of the Islamic Development Bank (IDB) in 1975. After that, the development of Islamic banking expanded to various countries, particularly in the Middle East, South Asia, and Europe. In Indonesia, Islamic banking institutions officially began operating in 1992 with the establishment of Bank Muamalat Indonesia (BMI), the first Islamic bank. The industry's development is strengthened by specific regulations, in the form of Law Number 21 of 2008 concerning Islamic Banking, which serves as a primary foundation for strengthening the sector. Currently, Islamic banking in Indonesia is starting to show significant growth thanks to government support, increasing awareness among Muslims, and product and service innovations that are able to compete globally. This historical journey demonstrates that Islamic banking has evolved beyond simply being an alternative option and has become a vital component of a healthy economic system, both nationally and internationally.